POOR HYPERTENSION CONTROL AND DISAPPEARANCE OF MEDITERRANEAN LIFE STYLE ON THE CROATIAN ADRIATIC ISLANDS. HUNT ON THE SILENT KILLER (HSK) – OPPORTUNISTIC PUBLIC HEALTH ACTION. (June 2022) - Tarnovski, Lorka; Frkanec, Stjepan; Katic, Luka; Strbac, Tea; Susnjara, Petar; Lovakovic, Josip; Kolaric, Melanija; Stupin, Ana; Josipovic, Josipa; Baretic, Maja; Boljesic, Marta; Begic, Zvonimir; et al.
Abstract : Objective: Mediterranean lifestyle is slowly disappearing along the Croatian coast and Croatian islands were supposed to be the last part of healthy living. Unfortunately, healthcare system is poorer on islands than in other parts of Croatia. Our aim was to analyse lifestyle and hypertension (HT) treatment and control among inhabitants of the Croatian islands. Design and method: HSK was organised by the Croatian Society of Hypertension and conducted by the WG- medical students in hypertension. A screening site was set up at the boat by which students traveled from island to island. Adult volunteers were recruited through opportunistic screening on five Adriatic islands. Trained medical students collected information through an extended questionnaire. HT was defined as blood pressure (BP) > 140/90mmHg (single occasion; an average of 2nd–3rd measurement; Omron M3) and/or self-reported use of drugs for HT. Results were compared with results from the general Croatian population (EHUH 2 cohort). Results: A total of 424 participants were included (196 men, average age 61 years). There were less obese and current smokers at islands than in the general Croatian population (26.5% vs. 33.1%; 21.5% vs. 25%, respectively, p < 0.05). Islanders were more physically active (> 1 time/week), eat more frequently fish (> 1 time/week), and use more frequently olive oil (daily basis) (44.1% vs. 26%, 79.9% vs. 32.5%, 72.6% vs. 14.9 %, respectively; p < 0.01). However, there were no differences in consumption of red meat, processed meat, cookies and cakes (p > 0.05). Less hypertensive patients were treated and control was achieved in less subjects on islands than in the general population (60.7% vs. 72.9%; 27.2% vs. 39.3%, respectively; p < 0.01). Conclusions: Some elements of Mediterranean life are still present on Croatian islands. However, several poor lifestyle habits are equally present on islands and in other Croatian regions. Treatment and control of HT are poorer on islands reflecting inadequate healthcare and lack of physicians. Public health authorities should reorganize health care on islands. In the meantime, such public health actions are warranted and must continue.